Tax neutrality and business taxation in Russia: A proposal for a consumption-based reform of the Russian income and profit tax - Dirk Kiesewetter (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2002)
The paper consists of 4 parts. I will start with defining the relevant aspects of tax neutrality. Then, I will evaluate general profit taxation in Russia with respect to its influence on economic decisions. The third part discusses the government bill for a simplified single tax for small businesses. In the last part, a proposal for reforming Russian profit taxation is presented that would make the income tax system neutral with respect to most business decisions.
urn:nbn:de:bsz:21-opus-18986
Keywords: 330; Unternehmen; Steuerrecht; Steuerneutralität; Russland; Ertragsteuer; Einkommensteuer; Besteuerungsgrundsatz; Steuerreform; Ausgabensteuer; Russland